"Do as I do, not as I say": Using social learning theory to unpack the impact of role models on students' outcomes in education. Issue 2 (20th December 2019) - Ahn, Janet N.; Hu, Danfei; Vega, Melissa
Abstract: Role modeling has received much attention in education research, uncovering the mechanisms by which imitation occurs (e.g., the aspects of role models that make them more or less effective) and identifying the outcomes associated upon imitating the model. Nonetheless, certain social‐cognitive processes involved in role modeling tend to be overlooked. This oversight is puzzling given that these processes, such as retention and reproduction of modeled behavior, are of great importance to role modeling processes—the consideration and inclusion of such processes can provide crucial insight. This paper provides an overview of the role model research in education to date, detailing researchers' focus and emphasis on identifying aspects of role model effectiveness. We then analyze how including the component processes of social learning or observational theory can add value and application to advance role modeling research. Finally, we provide recommendations to close the gap between current research trends and what has been previously theorized on modeling to help inform ongoing future investigations.